What New Zealanders find important to their quality of life: comparisons with international WHOQOL data from 14 other countries - Christian U. Krägeloh; Rex Billington; Patricia Hsien‐Chuan Hsu; Jason Landon (Elsevier, 2015)
Abstract Objective: When the World Health Organization Quality of Life tools were developed by 15 collaborating centres in 14 countries, respondents rated how important they considered various facets of health‐related quality of life. The present study compared quality of life importance ratings from New Zealanders with the global data collected 17 years earlier. Possible differences by gender and age were also explored. Methods: A WHOQOL importance questionnaire was posted to a random sample of 2,000 New Zealanders. The ratings from the 585 questionnaires that were returned were ranked in order of importance and compared with the rankings from the original WHOQOL work. Results: The overall pattern of rankings of importance items was strikingly similar to that of the global data. Some of the few differences included comparatively lower importance ratings by New Zealanders of the facet to be able to work and higher ratings of feeling physically safe and secure. Other differences in importance ratings were also noted by gender and age group. Conclusions: The overall high similarities of importance rankings with the global dataset suggest that the cross‐cultural validity of the instrument may still be current. The few observed differences could reflect aspects unique to New Zealand or the presence of global trends during the 17 years since the original WHOQOL work, highlighting the utility of periodic investigations into the need to update the instrument.